Аpplication of it-methods in maritime industry tasks - Хнюнін, Сергій Георгійович; Хнюнін, С. Г.; Khniunin, Serhii H.; Khniunin, S. H.; Shvedu, M. I.; Kolesnichenko, I. O. (Одеса : Видавничий дім «Гельветика», 2025)
This paper analyses the steady growth of the maritime industry across sectors of the economy, transport, and logistics sectors, alongside the increasing use of software products tailored to this field. At present, graduates of maritime higher education institutions are predominantly trained to use existing IT-solutions. While they often possess strong operational skills, they frequently lack expertise in programming, algorithm design, and applied software engineering. It is proposed that the curriculum for the specialty F2 speciality in "Software Engineering" include dedicated modules addressing maritime-specific challenges. This integration would unlock new prospects for the advancement of both education and the maritime industry.
Khniunin S. H. Аpplication of it-methods in maritime industry tasks / S. H. Khniunin, M. I. Shvedu, I. O. Kolesnichenko // Передові технології в інформаційно-комунікаційній інженерії (ATICE'2025) : матеріали Міжнародної конференції / за заг ред. С. В. Ківалова ; Міжнародний гуманітарний університет. – Одеса : Видавничий дім «Гельветика», 2025. – С. 20-24. - Режим доступу: https://doi.org/10.32837/11300.30176
Keywords: software engineering; maritime industry; software development; maritime engineer training